Selective Adsorption of Pb(II) from Aqueous Solution by Triethylenetetramine-Grafted Polyacrylamide/Vermiculite - Shiqing Gu (Laboratory of Environmental Sciences and Technology, Xinjiang Technical Institute of Physics & Chemistry, Key Laboratory of Functional Materials and Devices for Special Environments, Chinese Academy of Sciences, Urumqi 830011, China) (MDPI AG, 2018)
Amine groups play significant roles in polymeric composites for heavy metals removal. However, generating a composite with a large number of functional and stable amine groups based on clay is still a challenge. In this work, a new amine-functionalized adsorbent based on acid-activated vermiculite (a-Verm) was prepared by organic modification of silane coupling agent as bridge, followed by in situ polymerization of acrylamide (AM) and further grafting of triethylene tetramine (TETA). The obtained polymeric composite g-PAM/OVerm was characterized by scanning electron microscope (SEM), energy dispersive spectrometer (EDS), Fourier transform infrared (FTIR), thermal analysis (TG/DTG), X-ray photoelectron spectroscopy (XPS) and Brunauer–Emmett–Teller (BET) analyses, confirming that amine groups were successfully grafted onto the surface of Verm. The efficacy g-PAM/OVerm for removing Pb(II) was tested. The adsorption equilibrium data on g-PAM/OVerm was in good accordance with the Langmuir adsorption isotherms, and the adsorption maximal value of Pb(II) was 219.4 mg·g−1. The adsorption kinetic data fit the pseudo-second-order kinetic model well. Additionally, g-PAM/OVerm has better selectivity for Pb(II) ion in comparison with Zn(II), Cd(II) and Cu(II) ions. The present work shows that g-PAM/OVerm holds great potential for removing Pb(II) from wastewater, and provides a new and efficient method for the removal of heavy metal ions from industrial wastewater.